A influência da cultura e da comunicação para a geração de conhecimento em contexto organizacional - Santos, Cássia Dias [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (My University, 2013)
In the organizational context culture and communication are fundamental to the processes of appropriation, sharing, generation and use of knowledge. However, in organizations, it is evident that there is little awareness about the influence of information culture and informational communication in the scope of knowledge management. In this perspective and considering the theoretical context, we analyze the influence of culture and communication in the construction of knowledge in an organizational context. This study presents a qualitative research covering national literature focusing theoretical literature published about this thematic. Analyzing this literature we have verified that without an appropriate information culture and an appropriate information communication favoring the organizational processes, hardly the managers would reach the purpose of stimulating knowledge creation within the organization's environment. In conclusion we consider that culture and communication are the foundations for the effectiveness of activities that occur within the context of knowledge management.

No ambiente organizacional a cultura e a comunicação são fundamentais no que tange aos processos de apropriação, compartilhamento, geração e uso de conhecimento. No entanto, evidencia-se que há pouca percepção quanto à influência da cultura e da comunicação informacional no escopo da gestão do conhecimento. Nessa perspectiva, analisa-se a partir de um contexto teórico a influência da cultura e da comunicação na construção de conhecimento em contexto organizacional. Para tanto, realiza-se uma pesquisa bibliográfica de natureza qualitativa abrangendo a literatura nacional, cujo enfoque é explorar e resgatar conhecimentos teóricos disseminados sobre o tema. Constata-se que sem haver uma cultura e comunicação informacionais favoráveis aos processos organizacionais, dificilmente os gestores atingem o propósito de dinamizar o conhecimento gerado no ambiente da organização. Considera-se que a cultura e a comunicação são alicerces para a efetividade das atividades que ocorrem no âmbito da gestão do conhecimento.
The influence of culture and communication for the knowledge generation in an organizational context
Keywords: Cultura Informacional; Cultura Organizacional; Comunicação Informacional; Comunicação Organizacional; Gestão do Conhecimento